Judgments regarding parental alienation when parental hostility or child sexual abuse is alleged. Issue 4 (2nd October 2018) - Priolo-Filho, Sidnei; Goldfarb, Deborah; Shestowsky, Donna; Sampana, Janelle; Williams, Lucia C. A.; Goodman, Gail S.
Abstract: Allegations of Parental Alienation (PA), the systematic disparaging of one parent by the other parent aimed at alienating their child's affections, as a basis for child custody decisions are highly controversial. Claims of parental hostility or allegations of child sexual abuse in custody cases may trigger concerns about PA. Family court professionals ( N = 280) rated young children's accuracy of report (e.g., suggestibility, honesty) in general and also read three custody scenarios varying as to whether or not they included allegations of parental hostility or child sexual abuse, or no such allegations. For each scenario, the alleged alienating parent's gender was experimentally varied between subjects. Participants rated the likelihood that each case involved PA. For the scenario that included allegations of child sexual abuse, professionals who viewed young children as more inaccurate reporters or who read about the mother (rather than a father) as the alleged alienator were more likely to rate the scenario as involving PA. For the scenario that described parental hostility but no child sexual abuse allegations, professionals who were older or female were more likely to judge the scenario as involving parental alienation when a mother (rather than a father) was the alleged alienator, whereas there were no significant predictors of responses to the no-allegation scenarios. Findings are discussed in relation to the difficult task of evaluating custody cases for PA when parental hostility or child sexual abuse is alleged.